2013
DOI: 10.1111/1574-6941.12103
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of freshwater biofilms by nitrifying bacteria from activated sludge

Abstract: Effluents from wastewater treatment plants (WWTPs) containing micro-organisms and residual nitrogen can stimulate nitrification in freshwater streams. We hypothesized that different ammonia-oxidizing (AOB) and nitrite-oxidizing (NOB) bacteria present in WWTP effluents differ in their potential to colonize biofilms in the receiving streams. In an experimental approach, we monitored biofilm colonization by nitrifiers in ammonium- or nitrite-fed microcosm flumes after inoculation with activated sludge. In a field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 58 publications
4
35
0
4
Order By: Relevance
“…Nitrospira defluvii" and strain BS10 originated, nitrite concentrations of 7 to 8 M in activated-sludge samples (52) and 21 to 571 M in sewage influents (Hamburg Wasser, personal communication, 2014) were measured. Nitrospira bacteria have commonly been detected in oligotrophic ecosystems such as subsur- face fluids (53) and freshwaters with nitrite at nanomolar concentrations and below the detection limit, respectively (54,55). These findings and the oxidation kinetics measured in this study support the suggested classification of Nitrospira bacteria as K strategists (16).…”
Section: Discussionsupporting
confidence: 84%
“…Nitrospira defluvii" and strain BS10 originated, nitrite concentrations of 7 to 8 M in activated-sludge samples (52) and 21 to 571 M in sewage influents (Hamburg Wasser, personal communication, 2014) were measured. Nitrospira bacteria have commonly been detected in oligotrophic ecosystems such as subsur- face fluids (53) and freshwaters with nitrite at nanomolar concentrations and below the detection limit, respectively (54,55). These findings and the oxidation kinetics measured in this study support the suggested classification of Nitrospira bacteria as K strategists (16).…”
Section: Discussionsupporting
confidence: 84%
“…The NO 2 Ϫ and NO 3 Ϫ concentrations increased until day 7 and were stable subsequently. No NO 2 Ϫ accumulation was observed, possibly due to the presence of nitrite-oxidizing bacteria (NOB) in downstream sediments (54). The in vitro incubations used here differ from in-river conditions and, as a result, reflect only potential ammonia oxidation rates.…”
Section: Resultsmentioning
confidence: 94%
“…In addition, previous studies showed that typical microorganisms in WWTP systems could easily colonize the niche of native species in river sediments via effluent inputs (Mußmann et al 2013;Cébron and Garnier 2005). As the main drainage river of Beijing, Beiyun River receives large amounts of effluents from WWTP (Jing et al 2013).…”
Section: Discussionmentioning
confidence: 99%